Educational Images Included at the Content of Fiqh and Behavior Course for the Third Grade of Primary School in KSA: An Analytical Study - Ebrahem Khateeb (Umm Al-Qura University, 2023)
The current study aims at determining the criteria that should be taken into consideration when choosing educational images at the content of Jurisprudence and Behavior course for the third grade of primary school in KSA, and to identify the extent to which those educational images include the standards necessary for them, and how those standards are distributed according to the fields of study. To answer the questions of the study, the researcher used approach of descriptive based on the method of content analysis. The researcher built two tools: the first was the educational image analysis standard, while the second was the card for analyzing the educational images in light of the analysis standard. The study sample included all the educational images mentioned at the content of the course, with a number of (100) educational images. The study has come to a number of results, the most important of which are: the number of criteria that should be considered when choosing educational images at the content of the course reached (14) criteria, distributed into (3) areas, represented at the field of general educational standards for the educational image, the field of colors and attractiveness of the educational image, and the field of design and general output of the educational image. The results showed that the educational images included at the content of the course achieved (65.1%) of the standards necessary for it; meanwhile the field of design and general output of the educational image was the highest in terms of prevalence with a rate of (31.6%). The results of the study revealed the lack of a large number of educational images for a set of criteria, such as clarity of colors, simplicity, modernity and development in the subject it expresses.